Cinema e Educação: desmistificando a figura do cientista através do filme "Criação" - Silva, Thaís Aparecida da (Universidade Federal de São Carlos, 2017)
Given the difficulties of the educational system, new strategies seeking learning and teaching proposals have been suggested. Cinema stands as a possibility, because it is possible to convey information and raise the interest of the audience in a very effective way through the movies language. The outreach activity – ACIEPE: Cinema with Science (2016) was proposed to connect cinema and science through discussion of scientific issues informally addressed in the movies. Surveys were answered by the end of the exhibitions. The perceptions of the ACIEPE’s attendees on the movie “Creation” have been analyzed through a qualitative methodological approach. Common elements students speeches allowed the setting of categories. Results have established six categories based on the main aspects raised by the survey’s participants. Among them, the most relevant aspect (corresponding to 53% of responses) was related to the reason why people enjoyed the movie and referred to the humanized vision of the scientist depicted in the art piece. This contrasts with the stereotyped way scientists are usually portrayed by the media. The experience of watching a movie that shows a scientific personality, Charles Darwin, through a different approach has allowed everyone to be closer to a more natural and human view of the scientist. This highlights the cinema as an interesting didactics tool, because this art would assist in the teaching-learning process through its potential to deconstruction and reconstruction opinion.
Cinema and Education: deconstructing the scientist´s image with the film "Creation"
Keywords: Charles Darwin; popularização da ciência; ACIEPE; mídias como metodologia de ensino; recursos didáticos; science popularization; media as a teaching methodology; didactic resources; CIENCIAS HUMANAS::EDUCACAO